Transformasi Kaligrafi Klasik Ke Kaligrafi Digital: Kolaborasi Antara Tradisi Dan Teknologi - Rabiatul Adawiyah Madawat M (CV. SINAR HOWUHOWU, 2026)
This study examines the transformation of classical calligraphy into digital calligraphy as a form of collaboration between artistic tradition and modern technology. Through a qualitative approach with descriptive analysis methods, this research explores how calligraphy practitioners adapt traditional techniques to digital media using tools such as tablets, styluses, or laptops and specialized software like Photoshop, Procreate, Corel, and Ibis. The findings show that digital calligraphy does not replace classical calligraphy but rather serves as its extension, allowing for greater accessibility, preservation of heritage, and creative innovation. However, this transformation raises challenges regarding the preservation of authentic values and the development of new aesthetic standards. This study recommends the integration of digital learning in traditional calligraphy curricula to produce the next generation of calligraphers who are both technically skilled and digitally literate.